Design of a mandibular advancement device for patients with partial dentures - Park, S.-M.; Park, S.; Chio, H.; Kim, L.; Lee, S.H.; Noh, G. (Korean Society of Mechanical Engineers, 2018)
A mandibular advancement device (MAD) is a convenient means to treat obstructive sleep apnea by moving the mandible of the patient forward. However, the MAD may result in jaw joint disorders or unintentional tooth movement in patients with partial dentures. The objective of this study is to enhance the design of the MAD for patients with partial dentures. As the conventional MAD often results in complications, a density-based topology optimization technique is utilized to enhance the stability of the MAD. Topology optimization tasks are performed to minimize the strain energy and volume of the MAD as well as to reduce bone stress to a biomechanically stable range. ？ 2018 The Korean Society of Mechanical Engineers.
Keywords: Finite element method; Sleep research; Strain energy; Topology; Density-based; Design optimization; Fixed partial dentures; Mandibular Advancement Device; Obstructive sleep apnea; Optimization techniques; Partial dentures; Tooth movement; Dental prostheses